Pengaruh Digital Marketing, Online Customer Review, Price Discount Terhadap Keputusan Pembelian Produk Di Hampers_Quu Mojosari Mojokerto - Oktaviyanti, Vara; Asiyah, Siti; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze and evaluate the effect of digital marketing, online customer reviews, and discounts on purchasing decisions simultaneously and partially at Hampers_Quu Mojosari Mojokerto. this research uses a quantitative approach. A total of 80 people participated in this activity. validity and reliability tests were conducted to measure the performance of research questions as data collection tools. In addition, this study uses normality test, heteroscedasticity test, multicollinearity test, F test, R2 test and t test. The results of this study indicate that digital marketing, online customer reviews, and discounts simultaneously and partially have a positive and significant effect on purchasing decisions. Keywords: digital marketing, online customer review, price discount and purchasing decisions.